Retinal venular vessel diameters are smaller during ten days of bed rest - Saloň, Adam; Çiftci, Göktuğ Mert; Zubac, Damir; Šimunič, Boštjan; Pišot, Rado; Narici, Marco; Fredriksen, Per Morten; Nkeh-Chungag, Benedicta Ngwenchi; Sourij, Harald; Šerý, Omar; Schmid-Zalaudek, Karin; Steuber, Bianca; et al. (Scientific reports, 2023)
Older individuals experience cardiovascular dysfunction during extended bedridden hospital or care home stays. Bed rest is also used as a model to simulate accelerated vascular deconditioning occurring during spaceflight. This study investigates changes in retinal microcirculation during a ten-day bed rest protocol. Ten healthy young males (22.9 ± 4.7 years; body mass index: 23.6 ± 2.5 kg·m-2) participated in a strictly controlled repeated-measures bed rest study lasting ten days. High-resolution images were obtained using a hand-held fundus camera at baseline, daily during the 10 days of bed rest, and 1 day after re-ambulation. Retinal vessel analysis was performed using a semi-automated software system to obtain metrics for retinal arteriolar and venular diameters, central retinal artery equivalent and central retinal vein equivalent, respectively. Data analysis employed a mixed linear model. At the end of the bed rest period, a significant decrease in retinal venular diameter was observed, indicated by a significantly lower central retinal vein equivalent (from 226.1 µm, CI 8.90, to 211.4 µm, CI 8.28, p = .026), while no significant changes in central retinal artery equivalent were noted. Prolonged bed rest confinement resulted in a significant (up to 6.5%) reduction in retinal venular diameter. These findings suggest that the changes in retinal venular diameter during bedrest may be attributed to plasma volume losses and reflect overall (cardio)-vascular deconditioning.
Keywords: Retinal Artery; Bed Rest; arteria centralis retinae; vena centralis retinae; klid na lůžku; Humans; fluoresceinová angiografie; Retinal Vein; mužské pohlaví; Male; lidé; Retinal Vessels; Fluorescein Angiography; retinální cévy